2016
DOI: 10.1145/2934668
|View full text |Cite
|
Sign up to set email alerts
|

Adding Physical Objects to an Interactive Game Improves Learning and Enjoyment

Abstract: Can experimenting with three-dimensional (3D) physical objects in mixed-reality environments produce better learning and enjoyment than flat-screen two-dimensional (2D) interaction? We explored this question with EarthShake: a mixed-reality game bridging physical and virtual worlds via depth-camera sensing, designed to help children learn basic physics principles. In this paper, we report on a controlled experiment with 67 children, 4-8 years old, that examines the effect of observing physical phenomena and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Yannier et al showed that children used more meaningful gestures while explaining their predictions when they observed physical blocks in a mixed-reality game, compared to a screen-only version of the same game. This result suggests that children may be having more meaningful mental visualizations (demonstrated by the gestures they use) when they interact with 3D objects [30].…”
Section: Benefits Of Experiencing Physical Phenomenamentioning
confidence: 89%
See 2 more Smart Citations
“…Yannier et al showed that children used more meaningful gestures while explaining their predictions when they observed physical blocks in a mixed-reality game, compared to a screen-only version of the same game. This result suggests that children may be having more meaningful mental visualizations (demonstrated by the gestures they use) when they interact with 3D objects [30].…”
Section: Benefits Of Experiencing Physical Phenomenamentioning
confidence: 89%
“…In a recent study, Yannier et al showed that children observing physical towers in a mixed-reality game learned physics principles better and showed higher levels of enjoyment compared to students interacting with a solely virtual game on a laptop [30]. This result suggests that observing physical phenomena (along with mixed reality feedback on whether child predictions and physical results match) may enhance learning and enjoyment.…”
Section: Mixed Reality Environments For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Visitors of CH sites can touch, manipulate and interact with smart objects, for example to receive personalized information during the visit. Such interaction fosters the appropriation of CH content [7]: as recognized by some recent works [9], physical manipulation is indeed an effective supplementary channel for the visitor to gather and store information, since they are enabled to activate real-world knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…End-User Development (EUD) methodologies fit very well the requirement of letting end users, with or without expertise in computer programming, to tailor, customize and program their software [2,4,6] or ecologies of smart objects [9]. Our approach proposes a visual composition paradigm that facilitates the creation of Event-Condition-Action (ECA) rules required to synchronize the behavior of multiple objects [5].…”
Section: Introductionmentioning
confidence: 99%